PROFIT MANAGEMENT PRACTICES IN CONSUMER GOODS COMPANIES WITH PROFIT QUALITY AS INTERVENING - Sari, Petty Aprilia; Merida, Merida; Rays, Muh. (COMPETITIVE, 2024)
This study aims to demonstrate empirically how the influence of ownership structure, tax planning, earnings management and earnings quality, and to investigate whether ownership structure, tax planning affects earnings management through the quality of earnings as an intervening variable. The data used in this study were obtained financial data from the financial statements of each company. The analysis method is path analysis using multiple regression with EViews version 12. The population used in this study is consumer goods company listed on the Indonesia Stock Exchange in 2018-2021, with a total sample of 9 companies. This research found that the variable institutional ownership, managerial ownership has no effect on earnings management, while tax planning have a effect on earnings management. Variable institutional ownership, managerial ownership has no effect on earnings quality, while tax planning have a effect on earnings quality. Earnings quality have negative influence the earnings management. The relationship of ownership structure variables in this case only institutional ownership, managerial ownership had no effect on the earnings management through quality of earnings as an intervening variable, while tax planning have a effect on the earnings management through quality of earnings as an intervening variable.